(untitled) (AUN INTERNATIONAL CONFERENCE, 2024)
The rise of Boko Haram activities in Northern Nigeria, particularly in the North-East, has led to frequent killings and the destruction of both public and private property, especially in areas like Yobe and Maiduguri. The safety of lives and property in this region is no longer guaranteed. In this study, we proposed and examined a stochastic model to understand and manage the dynamics of Boko Haram insurgency alongside counter-terrorism operations. We derived the differential equations that form the basis of the model and conducted simulations using the adaptivetau package in R. The findings indicate that counter-terrorism strategies have a significant effect on combating Boko Haram insurgencies. Consequently, we recommend that the Nigerian Army, with substantial support from the Air Force, intensify efforts to overcome the Boko Haram insurgency, including the acquisition of modern weaponry, the establishment of vigilante groups, and the implementation of rehabilitation programs to maintain the defeat of Boko Haram